KINERJA KELEMBAGAAN DAN TRANSPARANSI HARGA PADA PASAR LELANG CABAI MERAH DI KABUPATEN KULON PROGO (JASEP, 2015)
Auction market is one of the alternative strategies that can be done by farmers to improve the bargaining position of the middleman. In the implementation of the auction market, auction officers are required to work in a professional manner so that no one feels aggrieved. This study aims to determine the performance of institutional auction market and price transparency in red chili auction market in Kulon Progo. The method used is descriptive method or a combination of mixed methods research that combines qualitative methods with quantitative methods. Qualitative research carried out by means of in-depth interviews (depth interview) to the informant in the auction market. Quantitative research using questionnaires. The results showed that the performance of red chili auction market in Kulon Progo is very well proven with good management system as well as the perception of farmers and traders on the performance of the board who expressed very well by 81.5%. In addition, the perception of farmers and traders on the implementation of the auction market is also expressed very well, which means that the auction market has implemented the principle of auction market so as market worth mentioning that tansparence